YIELD, QUALITY AND WATER CONSUMPTION OF CONILON COFFEE UNDER IRRIGATED AND DRYLAND MANAGEMENTS - Dardengo, Maria Christina Junger Delôgo; Pereira, Lucas Rosa; Sousa, Elias Fernandes de; Reis, Edvaldo Fialho dos (Coffee Science - ISSN 1984-3909, 2018)
In this study the goal was to make an assessment and comparison of the yield, quality and water consumed by the Conilon coffee plants under irrigated and dryland types of cultivation, from seedlings raised in different containers and under varying shading levels. The experiment which extended from December 2007 to April 2012 was performed at the IFES, Alegre-ES Campus and involved the study of a total of four crops. The findings showed that the irrigated plants had 162% higher yield on average than did the rainfed plants. For the irrigated plants, the yield indices achieved were 4.5 kg of coffee of the planted / benefited area; 1.9 kg of coconut / beneficiated coffee and 5.6 balms of 80 L sc-¹; whereas, for the rainfed plants, the values recorded were 8.2 kg of coffee from the benefited field; 3.1 kg of coconut / beneficiated coffee and 12 balloons of 80 L sc-¹. The Conilon coffee grains harvested from the irrigated plants were superior in quality to those from the rainfed plants. For the irrigated plants, the water consumed on average was 7.9 m3 per plant, while for the rainfall-dependent crop, it was 4.95 m3. For the irrigated and rainfed plants the relations between the water consumption / kg of the beneficiated coffee was 8.8 m3 and 30.3 m3, respectively. The type of container and levels of shading exerted no influence on the Conilon coffee with respect to productivity, yield and quality.